Standard Operating Procedures Design and Development for Alcoffee Coworking Space - Melvin Tioris; Adi Neka Fatyandri (Universitas Internasional Batam, 2023)
Alcoffee Coworking Space is a halal cafe and restaurant with a blend of three cultures, namely Indonesia, Japanesse and Western, and Alcoffee also presents a variety of food menus inspired by various cultures in the world. In a work activity within the company, there is a need to avoid work errors. The work errors usually do not have the SOP (Standard Operation Procedure) and this also affects the continuity and smoothness of a company. From this side it can be seen that in the SOP (Standard Operation Procedure) the company can help the company's partners as well as on the consumer or visitor side, the advantage of the SOP (Standard Operation Procedure) for the company is that the company will always be applied for its discipline while, for the visitors will get service good and comfortable so that visitors will feel satisfied with the cafe. The research subject is a waiter at Alcoffee Coworking Space and the object of his research is the SOP for service, supervision and training for customer satisfaction. Knowing the identity of the work activities of Alcoffee employees, the preparation and design of SOP that are in accordance with the needs of employees so that they can work better and efficiently according to their position.The design of the output of this activity is intended to be able to find an expected outcome. The output of this activity is to provide support to the Alcoffee Coworking Space company regarding the importance of Standard Operational Procedure for the company and especially for staff and employees.With the achievement of customer desires and satisfaction due to every good treatment from employees, it will certainly eliminate the occurrence of customer distrust of the company's image, because it is necessary to maintain the quality of each and even improve the quality of the staff so that they will always develop better.